Effect of Woody Biomass Gasification Process Conditions on the Composition of the Producer Gas - Alejandro Lyons Cerón (MDPI AG, 2021)
Using woody biomass in thermochemical gasification can be a viable alternative for producing renewable energy. The type of biomass and the process parameters influence the producer gas composition and quality. This paper presents research on the composition of the producer gas from the gasification of three woody biomass species: spruce, alder, and pine. The experiments were conducted in a drop-tube reactor at temperatures of 750, 850, and 950 °C, using air as the gasifying agent, with equivalence ratios of 0.38 and 0.19. Gas chromatography with a thermal conductivity detector was used to determine the composition of the producer gas, while the production of total organic compounds was detected using Fourier-transform infrared spectroscopy. All three wood species exhibited very similar producer gas composition. The highest concentration of combustible gases was recorded at 950 °C, with an average of 4.1, 20.5, and 4.6 vol% for H2, CO, and CH4, respectively, and a LHV ranging from 4.3–5.1 MJ/m3. The results were in accordance with other gasification studies of woody species. Higher temperatures enhanced the composition of the producer gas by promoting endothermic and exothermic gasification reactions, increasing gas production while lowering solid and tar yields. The highest concentrations of combustible gases were observed with an equivalence ratio of 0.38. Continuous TOC measurement allowed understanding the evolution of the gasification process and the relation between a higher production of TOC and CO as the gasification temperature raised.